Coaromatization of methane and propane over Ga supported on HZSM-5 catalysts: The effect of mesoporosity on deactivation behavior. (15th November 2021) - Yeong Gim, Min; Hyun Lim, Yong; Lee, Kwan-Young; Heui Kim, Do
Graphical abstract: Highlights: GaOy /meso-HZSM-5 and GaOy /micro-HZSM-5 catalysts were prepared. Co-aromatization of methane and propane was performed to produce BTX. The effect of mesoporosity on the deactivation behavior was investigated. The interaction strength between coke and acid sites is different in each catalyst. Abstract: Ga supported on mesoporous HZSM-5 (GaOy /meso-HZSM-5) and conventional HZSM-5 (GaOy /micro-HZSM-5) catalysts were compared to investigate the effect of mesoporosity on the deactivation behavior in the coaromatization of methane and propane. The trend of reaction intermediate distribution between the catalysts became gradually different with time-on-stream, implying a distinction in deactivation behavior. These are attributed to the behavior of acid site blockage, because the production of BTX are driven by acid sites. The reaction with 13 CH4 and further analyses revealed that the interaction between coke and Ga species that serve as Lewis acid sites is much stronger in GaOy /micro-HZSM-5 than in GaOy /meso-HZSM-5 post-reaction catalyst. Therefore, large amount of highly condensed coke was deposited in GaOy /micro-HZSM-5 during the reaction, leading to fast catalyst deactivation. Consequently, the structural difference arising from mesoporosity affects physicochemical properties of the catalysts thereby contributing to different deactivation behavior between the catalysts.